Collaboration and Teamwork are Required for Successful Maternity Care Quality Improvement. Issue 6 (November 2016) - N/A,
Abstract : The articles in the special issue on maternity quality care improvement offer valuable information and suggestions for promoting safe care for mothers and babies during their hospitalization. Each of the projects described involved multidisciplinary collaboration and teamwork as keys to success.